Role of tumor necrosis factor-alpha in the central nervous system: a focus on autoimmune disorders - Gonzalez Caldito, Natalia (Frontiers in Immunology, 2023)
Tumor necrosis factor-alpha (TNF-α) is a pleiotropic immune cytokine that belongs to the TNF superfamily of receptor ligands. The cytokine exists as either a transmembrane or a soluble molecule, and targets two distinct receptors, TNF-α receptor 1 (TNFR1) and TNF-α receptor 2 (TNFR2), which activate different signaling cascades, and downstream genes. TNF-α cellular responses depend on its molecular form, targeted receptor, and concentration levels. TNF-α plays a multifaceted role in normal physiology that is highly relevant to human health and disease. In the central nervous system (CNS), this cytokine regulates homeostatic functions, such as neurogenesis, myelination, blood-brain barrier permeability and synaptic plasticity, but it can also potentiate neuronal excitotoxicity and CNS inflammation. Physiological levels of the cytokine are beneficial and protective to the human brain, whereas its excess can be deleterious and lead to chronic inflammation and cause autoimmune disorders. Administration of anti-TNF-α therapy is beneficial in certain disorders such as neurosarcoidosis and neuro-Behçet disease, but detrimental in multiple sclerosis. This article is focused on describing the various roles, physiological and pathological, of TNF-α in the CNS. In addition, it discusses the specific disease processes that are dependent or regulated by TNF-α, and the rationale of its use as a therapeutic target.